Climate-friendly food-choice intentions among emerging adults: extending the theory of planned behavior with objective ambivalence, climate-change worry and optimism - Jylhä, Kirsti M.; Ojala, Maria; Odisho, Sandy; Riise, Anja (Frontiers in Psychology, 2023)
Climate-friendly food choices are still relatively rarely addressed in studies investigating climate engagement, particularly among young people. We therefore examine which factors correlate with intentions to make these choices among emerging adults. Our overarching theoretical framework is the Theory of Planned Behavior (TPB), which we extended with emotional factors (climate-change worry and optimism) and attitudinal ambivalence. We found that all factors included, except for optimism, correlated with the food-choice intentions. Climate-change worry was the second strongest predictor, after attitudes. Moreover, a measure of objective attitudinal ambivalence correlated negatively with food-choice intentions and moderated the correlation between attitudes and intentions by weakening it. The results support the validity of using the TPB model when explaining intentions to make climate-friendly food choices among young people. However, our results suggest that it is also important to consider emotions—in this case climate-related worry—and the existence of conflicting evaluations about choosing climate-friendly food.